Effect of organo-montmorillonite on mechanical properties of bismaleimide composites reinforced by glass fibre and carbon fibre. (14th May 2015) - Li, W.; Wang, M. Y.; Zhao, H. W.; Zhou, B. Q.; Ren, R.
Abstract : Organo-montmorillonite (OMMT) modified bismaleimide (BMI) nanocomposites were used as the matrix of glass fibre and carbon fibre reinforced composites. The effects of OMMT on the mechanical properties of BMI resin and fibre composites were investigated. Fourier transform infrared spectroscopy (FT-IR) analysis revealed that there exist interactions between OMMT and resin, which is useful for the delamination and dispersion of the silicate layers within the BMI matrix. Owing to the incorporation of OMMT, the impact strength, flexural strength and modulus of BMI resin were substantially improved. Moreover, the interlaminar shear strength (ILSS), flexural strength and modulus of fibre composites were enhanced. Scanning electron microscopy (SEM) photographs exhibited that the destruction modes of fibre composites were changed from interfacial destruction into the matrix destruction after the introduction of OMMT. In addition, it was found that the interfacial adhesion of glass fibre composite was improved more significantly than that of carbon fibre composite.